Gastroprotective effect of Alhagi maurorum (camel thorn) in ethanol-induced gastric damage in mice - Gargoum , Huda M.; Ejjhawe , Zubeida A.; Abellatif , Awad G; El-Mahjoob, Sana M. (Scientific Journal of University of Benghazi, 2022)
Background: Alhagi maurorum is a medicinal plant found in different regions of the world including the eastern part of Libya. Aim: It is widely used in liver diseases with its hepatoprotective activity but its effect as an anti-ulcerogenic is not known locally. This study was undertaken to investigate the anti-ulcer effect the Alhagi maurorum has. Methods: A camel thorn extract (CTE) was prepared and administered to a group of mice for five days before they received ethanol to induce gastric ulcers. Comparable groups were a negative control group of mice that received normal saline and a positive control group of mice that received ethanol. The histopathological study of all stomachs was performed and graded according to the lesion scoring system. Result: Statistically, the mice that received CTE showed a significant improvement in the lesion score as compared to the animals that received ethanol. Conclusion: We conclude the Alhagi maurorum has gastroprotective activity against ethanol-induced gastric ulcers.